2018
DOI: 10.1108/ijbm-10-2016-0145
|View full text |Cite
|
Sign up to set email alerts
|

E-banking in Colombia: factors favouring its acceptance, online trust and government support

Abstract: Purpose The purpose of this paper is to examine the adoption of e-banking in Colombia, including a comprehensive analysis of consumer trust in this type of transaction and of the impact of the current government policy to promote e-commerce. Design/methodology/approach An empirical investigation based on the UTAUT2 model collected data from throughout the country to develop 600 online questionnaires. Findings The proposed model was validated in that the factors hypothesised to build trust in the use of ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 40 publications
8
61
2
2
Order By: Relevance
“…I believe Fintech services keep my personal information safe. Chong et al [62] and Sanchez et al [72] Overall I believe Fintech services are trustable.…”
Section: Trust (Tru)mentioning
confidence: 99%
See 1 more Smart Citation
“…I believe Fintech services keep my personal information safe. Chong et al [62] and Sanchez et al [72] Overall I believe Fintech services are trustable.…”
Section: Trust (Tru)mentioning
confidence: 99%
“…In the design of the questionnaire, this paper made full reference to the problems of domestic and foreign scholars in relevant research and made appropriate expansions and adjustments according to the characteristics of Fintech services studied in this paper, as shown in Table 2. PU was adopted from Lockett et al and Huh et al [68,69]; PEU was adopted from Cheng et al and Wang et al [70,71]; TRU was adopted from Chong et al and Sanchez et al [62,72]; BI was adopted from Ha et al and Ruparelia et al [73,74]; PR, GS, UI, ATT, and INT were adopted from Marakarkandy et al, Grabner-Kr et al, Zhang et al,and Patel et al [19,64,75,76]. The scale consisted of nine latent variables as external influencing factors, and each variable was composed of two to six measurement variables.…”
Section: Instrument Developmentmentioning
confidence: 99%
“…The positive and significant relationship between this variable and use behavior has been confirmed in different literature reviews ( Khechine et al., 2016 ; Williams et al., 2015 ). Behavioral intention was found to significantly and positively predict the use of established digital payment systems ( Sivathanu, 2018 ), mobile app-based shopping ( Savita Panwar, 2017 ), adoption of Internet banking ( Martins et al., 2014 ; Sánchez-Torres et al., 2018 ), and the use of m-banking ( Al Mashasba and Othman Nassar, 2012 ; Oliveira et al., 2014 ; Yu, 2012 ). The use of new technological systems can also be predicted by the intention to use it ( Venkatesh and Zhang, 2010 ) and consequently increasing online purchases intention ( Pavlou, 2003 ; Pavlou et al., 2007 ; Perea y Monsuwé et al., 2004 ; Sheppard et al., 1988 ; Sing and Matsui, 2017 ).…”
Section: Theoretical Framework and Hypothesis Modelmentioning
confidence: 99%
“…Moreover, government regulations can either encourage or hinder the adoption of innovation [49]; the government can provide financial incentives and assist in training personnel with logistics skills to promote the more efficient use of RFID [27], while, on the other hand, the severe intervention of governments and some bureaucracies has limited the diffusion of Information and Communications Technology (ICT), and both excessive intervention and nonsupport limit the development of new technologies. Sánchez-Torres et al [50] argued that government support is indispensable for the successful implementation of e-learning projects. In addition, previous studies have confirmed that government support has a significant impact on the adoption of innovative information technologies [50][51][52].…”
Section: Government Supportmentioning
confidence: 99%
“…Sánchez-Torres et al [50] argued that government support is indispensable for the successful implementation of e-learning projects. In addition, previous studies have confirmed that government support has a significant impact on the adoption of innovative information technologies [50][51][52].…”
Section: Government Supportmentioning
confidence: 99%